Privasi Data dan Perlindungan Hak Warga Negara dalam Praktik Media Sosial di Indonesia: Pendekatan Sosio-Legal - Ramadhan, Farhan Alif; Aisyah Nuraini, Siti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The development of social media in Indonesia has increased the intensity of the collection, processing, and dissemination of citizens' personal data. This situation raises the risk of privacy violations, data misuse, and the weakening of constitutional rights protection. This article analyzes data privacy protection practices in social media use in Indonesia using a socio-legal approach. This research examines the relationship between legal norms, user social behavior, and state institutional capacity following the enactment of Law Number 27 of 2022 concerning Personal Data Protection. The research method uses a normative juridical approach enriched by socio-legal analysis through a review of laws and regulations, legal doctrine, and empirical findings from previous studies. The results show a gap between the normative design of personal data protection and privacy protection practices on social media platforms. Law enforcement is inconsistent, public privacy literacy remains low, and oversight mechanisms are not functioning optimally. This article emphasizes that data privacy protection depends not only on formal legal instruments but also on social structures, user awareness, and state legal policy. These findings are relevant as a basis for strengthening personal data protection policies oriented towards protecting citizens' rights in Indonesia's digital space.